2020
DOI: 10.3390/molecules25020351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orange Extracts on Longevity, Healthspan, and Stress Resistance in Caenorhabditis elegans

Abstract: Orange, with various bioactive phytochemicals, exerts various beneficial health effects, including anti-cancer, antioxidant, and anti-inflammatory properties. However, its anti-aging effects remain unclear. In this study, the Caenorhabditis elegans (C. elegans) model was used to evaluate the effects of orange extracts on lifespan and stress resistance. The results indicated that orange extracts dose-dependently increased the mean lifespan of C. elegans by 10.5%, 18.0%, and 26.2% at the concentrations of 100, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 45 publications
1
32
0
4
Order By: Relevance
“…GST acts as both antioxidant enzyme and conjugates sulfhydryl (–SH) with xenobiotics for onward detoxification and elimination (Mazzetti et al., 2015). Previous studies have also shown that tropical functional foods such as turmeric, ginger, soy, gingko biloba increased GST activity as one of their antioxidant properties (Niedzielska et al., 2016; Wang et al., 2020). Furthermore, this study also revealed an increase in catalase activity in flies fed with diets supplemented with the citrus peels.…”
Section: Discussionmentioning
confidence: 98%
“…GST acts as both antioxidant enzyme and conjugates sulfhydryl (–SH) with xenobiotics for onward detoxification and elimination (Mazzetti et al., 2015). Previous studies have also shown that tropical functional foods such as turmeric, ginger, soy, gingko biloba increased GST activity as one of their antioxidant properties (Niedzielska et al., 2016; Wang et al., 2020). Furthermore, this study also revealed an increase in catalase activity in flies fed with diets supplemented with the citrus peels.…”
Section: Discussionmentioning
confidence: 98%
“…The effects of plant materials on gene regulation have been shown in numerous experiments on model organisms and cancer cell lines. It was shown that licorice and orange extract provoke enhancement of catalase activity and also extend Caenorhabditis elegans life span [ 85 , 86 ]. Citrus and apple pectin’s have induced the expression of genes involved in DNA repair ( D-Gadd, mei-9, spn-B ), apoptosis (wrinkled/hid) and heat shock response ( hsp70Aa ) in Drosophila [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Q3M is a avonoid abundant in onion peel that was found to extend the lifespan of C. elegans 39 . In the same study, even although rutin was found to improve the tolerance of C. elegans to oxidative stress, which is desirable for longevity , rutin had no affect the worm's lifespan 39 showed that orange extracts, where hesperidin was the predominant phenolic compound, increased the mean lifespan of C. elegans 43 . In the same study, orange extracts were also found to promote longevity by enhancing motility and reducing the accumulation of age pigment and ROS levels 43 .…”
Section: Flavonoidsmentioning
confidence: 96%